Legal Protection for the Winners of the Execution of Mortgage Rights in the Auction Case of Blocking of Property Rights Certificates (SHM) which Become the Object of the Auction - Rizky Melani Dian Pratiwi; Hanif Nur Widhiyanti; Diah Aju Wisuwardani (Jurnal Multidisiplin Madani, 2023)
The purpose of this study is to examine the meaning of the phrase "object of dispute in court" in the provisions of Article 45 paragraph 1 letter e of Government Regulation No. 24 of 1997 concerning Land Registration and In the event that the auction object is blocked, the winning bidders have legal protection when exercising their mortgage rights. Researchers employed a normative juridical research style in this study. The study's findings demonstrate that various parties have different interpretations of Letter E of Article 45 of PP Number 24 of 1997. Land Offices, so that any object of claim including objections to auctions because the limit value is considered low is still used as a reason to refuse registration of a rights transfer by auction. The type of law protection for auction winners, namely preventive protection which is preventive in nature, is still very weak, where The only thing the auction winner can do is wait for the Court's ultimate ruling. Taking legal action is another option to restrictive legal protection. The winning bidder may seek the District Court for help in removing the item. The auction winner can sue Perbuatan Melawan Hukum (PMH) against the Blocking Applicant and The representative for the to conduct the auction is the Land Office. in order to make the seller accountable through payment of damages. the blocking record